2020
DOI: 10.1371/journal.pone.0239191
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and factors associated with treatment failure among HIV infected adolescent and adult patients on second-line antiretroviral therapy in public hospitals of Northern Ethiopia: Multicenter retrospective study

Abstract: Background This study aimed to determine the incidence and factors associated with treatment failure among HIV infected adolescent and adult patients on second-line antiretroviral therapy (ART) in public hospitals of Northern Ethiopia. Methods A retrospective study was conducted from September 1, 2007 to July 30, 2017 on 227 patients. The data were extracted using a retrieval checklist from the patient's charts. The incidence rate of treatment failure was calculated using Kaplan-Meier methods and Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
4
28
1
Order By: Relevance
“…Statistical results are expressed using medians and inter-quartile ranges while regression analyses reported using adjusted hazard ratios, confidence intervals and p-value whose significance was taken as less than 0.05. We selected variables for testing based on findings from similar previous studies [ 6 , 8 11 , 16 , 18 20 , 24 ]. All p-values greater than or equal to 0.001 are reported as they are while p-values less than 0.001 are expressed as p < 0.001.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical results are expressed using medians and inter-quartile ranges while regression analyses reported using adjusted hazard ratios, confidence intervals and p-value whose significance was taken as less than 0.05. We selected variables for testing based on findings from similar previous studies [ 6 , 8 11 , 16 , 18 20 , 24 ]. All p-values greater than or equal to 0.001 are reported as they are while p-values less than 0.001 are expressed as p < 0.001.…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric treatment options are further restricted due to lack of approval, availability of formulations compatible for use by children and fixed-dose combinations. This has been shown to contribute for persistence of children on failed first line antiretroviral drugs and subsequent failure of second line regimens after a brief treatment duration [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a multicenter study conducted in Northern Ethiopia, the failure rate of second-line treatment was found to be 72.3% per 1000 person years (95% confidence interval: 55.75–93.71). 19 …”
Section: Introductionmentioning
confidence: 99%
“…Residence, age, educational status, co-morbidity, HIV disclosure status and CD4 count were associated with adherence. 17 , 18 Social support, absence of depression, and absence of substance use were also reported as determinants of adherence to CART. 19 Many studies were conducted on predictors of poor adherence separately but not associated with its effect on second-line regimens.…”
Section: Introductionmentioning
confidence: 99%